Circular RNA Splicing - Eger, Nicole; Schoppe, Laura; Schuster, Susanne; Laufs, Ulrich; Boeckel, Jes-Niels (Circular RNAs, 2018)
Circular RNAs (circRNAs) are covalently closed single-stranded RNA molecules derived from exons by alternative mRNA splicing. Circularization of single-stranded RNA molecules was already described in 1976 for viroids in plants. Since then several additional types of circular RNAs in many species have been described such as the circular single-stranded RNA genome of the hepatitis delta virus (HDV) or circular RNAs as products or intermediates of tRNA and rRNA maturation in archaea. CircRNAs are generally formed by covalent binding of the 5' site of an upstream exon with the 3' of the same or a downstream exon. Meanwhile, two different models of circRNA biogenesis have been described, the lariat or exon skipping model and the direct backsplicing model. In the lariat model, canonical splicing occurs before backsplicing, whereas in the direct backsplicing model, the circRNA is generated first. In this chapter, we will review the formation of circular RNAs and highlight the derivation of different types of circular RNAs.
Gesehen am 19.02.2020